Prinsip Pengembangan RPP Berbasis Karakter dalam Mata Pelajaran Pendidikan Agama Islam - Fibriyan Irodati (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
Every teacher is expected to integrate cultural values ​​and national character into the subjects taught, where the integration process has been outlined in the character education master design of the Ministry of National Education, which also emphasizes characterizing documents ranging from SK-KD analysis of content standards developed to in the syllabus and lesson plans. However, it is necessary to ask whether the teachers who play a role in integrating the characters in their lessons have an understanding of the characters? This is where the principle of character-based RPP development takes an important role for the implementation of cultural values ​​and national character in today's character education. This study aims to describe and analyze the principles of developing character-based lesson plans in Islamic religious education subjects. The results of the study show that the principle of developing character-based lesson plans in Islamic religious education subjects is that lesson plans must be able to be implemented in learning activities and in the formation of the character of students, support and be in accordance with the basic competencies that have been determined, pay attention to the material used as study material and there must be coordination between implementing components. program at school.